El encuentro de Foix y Dalí en las avenidas subterráneas del pre-sueño - Santamaria de Mingo, Vicent (Escritura e Imagen, 2007)
Before joining the Surrealist Group in Paris at the end of 1929, Dalí underwent the influence of the poet J.V. Foix, with whom he coincided in the mythical Catalan magazine L’Amic de les Arts. In it, the two friends, although of different generations, had the opportunity to gradually reveal their fascination for Surrealism and, more particularly, for those hypnagogic images that Breton took to be the starting point of Surrealist activity. Contributing enormously to the interest in these kinds of images was the book by Dr. Eugène Bernard Leroy, Les Visions du demi-sommeil, a book totally unknown to experts on both Foix and Dalí, yet whose impact was undoubtedly decisive for the first and most probably for the second, too.